PROMOTING MULTILINGUAL READER IN EFL CLASSROOMS: A PORTRAIT ON THE READING STRATEGIES - Lala Bumala (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2014)
This paper reports on how English as a Foreign Language Learner (EFL learners) explored their reading strategis when dealing with L1 and L2 texts. The destination of reading, a notion called comprehension, is by no means is a complicated process. This complexity can only be simplified only if a reader can employ the available reading strategies. The capacity to employ and develop the 20 reading strategies, as suggested by Grabe and Stoller (2002), can be injected both in L1 and L2 context. In EFL reading context, comprehension must first take place in students’ first language (L1), and eventually lead to comprehension in their second language (L2) (Alwasilah 2012; 2001). From this perspective, EFL classroom now serves as a ‘sacred’ site for promoting multilingual reader in which students are encouraged to demonstrate engagement dynamically both in their L1 and L2. From the 20 strategies employed by two selected respondents, four strategies seem to be a big puzzle for EFL leerners: focus on generic structure, intertextuality, inferences, and discourse markers. This, however, should be seen as a milestone rather than as a weakness. The more strategies employed, the more strategic the readers will be. This is the phenomenon captured in EFL reading classroom presented in this study. Keywords: L1 and L2 reading, strategic reading, comprehension.